Quantitative evaluation of apically extruded debris during root canal preparation with reciprocating single file system, continuous rotary multiple file system and manual technique: An in vitro study - Pratima Mohana; Dax Abraham; Alka Gurawa; Alpa Gupta; Parul Chauhan; Arundeep Singh; Sucheta Jala (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of the study is to evaluate and compare the quantity of apical debris extrusion from the root canals during biomechanical preparation by various rotary (reciprocating, Protaper Next [PTN] continuous) and manual hand filing system and by means of Crown-Down and Step Back techniques. Materials and Methods: Eighty mature, human mandibular premolars with single canals were randomly divided into four groups of twenty teeth each. Each group was instrumented using one of the four instrumentation systems: Group A: WaveOne, Group B: PTN, Group C: Hand file with Crown Down, Group D: Hand file with Step Back. Extruded debris was collected in preweighed Eppendorf tubes and the extruded irrigant was evaporated. The weight of the dry extruded debris was established by comparing the pre and post-instrumentation weight of Eppendorf tubes for each group. Results: Mean comparison of groups in different instrumentation by ANOVA presented that hand file with Step-Back technique is showed maximum amount of apical extrusion debris and continuous rotary file system showed the minimum amount of extrusion debris (P < 0.001). Conclusions: The current ex vivo study demonstrated reciprocating single file WaveOne and continuous rotary multiple file system lead to significantly less debris extrusion than manual hand file techniques. Reciprocating single file WaveOne extruded more debris than continuous rotary PTN multiple file system. More amount of debris was extruded in the group with Step-Back hand filing than Crown-Down technique.